Universal scaling in BCS superconductivity in three dimensions in non-s waves - Ghosh, A. [UNESP]; Adhikari, S. K. [UNESP] (Springer Nature, 1998)
The solutions of a renormalized BCS equation are studied in three space dimensions in s, p and d waves for finite-range separable potentials in the weak to medium coupling region. In the weak-coupling limit, the present BCS model yields a small coherence length ξ and a large critical temperature, T c, appropriate for some high-T c materials. The BCS gap, T c, ξ and specific heat C s(T c) as a function of zero-temperature condensation energy are found to exhibit potential-independent universal scalings. The entropy, specific heat, spin susceptibility and penetration depth as a function of temperature exhibit universal scaling below T c in p and d waves.
Keywords: 74.20.Fg BCS theory and its development; 74.72.-h High-T c compounds; Condensation; Entropy; Mathematical models; Specific heat of solids; Superconducting transition temperature; Superconductivity; Thermal effects; Bardeen Cooper Schrieffer theory; High temperature superconductors